Geology, structure and age of the Nahuel Niyeu Formation in the Aguada Cecilio area, North Patagonian Massif, Argentina - Greco, Gerson Alan (2015)
Fil: Greco, Gerson Alan. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Patagonia Norte; Argentina.